Analysis of the Use of Example Non Example Learning Strategies in Religious Subjects - Hardiansyah; Alliyah Putri (Yayasan Zia Salsabila, 2023)
The aim of the research is to find out the example non example learning process. An example non example learning strategy is a learning strategy that provides examples in the form of pictures, as well as cases that contain problems to be analyzed and then described until it is concluded by students. Through the example non example learning model the teacher provides opportunities for students to find their own ideas. This study used qualitative research methods. Qualitative research is data obtained from observations, interviews, analysis, documentation, field notes not set forth in the form of numbers. The results of research using the example non example strategy are very easy for students to understand and understand, the example non example learning model can improve student learning outcomes and can improve critical thinking skills. Using an example non example learning strategy makes children more active in learning.